Genetic analysis of spathoglottis species in Peninsular Malaysia / Florence C Ginibun @ Camillus - Florence C, Ginibun @ Camillus (2016)
A study was conducted to characterize the five native Malaysian Spathoglottis species of Spathoglottis aurea, Spathoglottis affinis, Spathoglottis gracilis, Spathoglottis microchilina and Spathoglottis plicata by morphological characteristics and molecular techniques. Three molecular markers were used namely; Inter Retrotransposon Amplified Polymorphism (IRAP), DNA barcoding and Amplified Fragment Length Polymorphism (AFLP). Two distinct morphological traits of flower colour and lip shape were selected from 47 qualitative characteristic to distinguish the species. The morphological characterisation was supported by molecular technologies using nuclear and chloroplast DNA markers. The nuclear marker consists of IRAP and AFLP technique. Both techniques amplified high polymorphism banding pattern where they form 341 polymorphic bands and later produce 891 polymorphic bands. The markers were also supported by the chloroplast DNA marker with the same clustering pattern based on the species. First cluster comprised of S. plicata while the second cluster comprised of S. aurea, S. gracilis, S. affinis and S. microchilina. The dendrogram generated by three different molecular markers showed consensus in the clustering pattern. The clustering pattern for the five native Spathoglottis species was in accordance with their flower colour where S. plicata is purple in colour and the other four species of Spathoglottis are yellow in colour. Spathoglottis plicata was a chosen species for a population study to evaluate the genetic structure based on geographical location for conservation and management purposes. A total of 11 AFLP markers of EcoRI+3 bases/MseI+3 base primer combinations give rise to 279 polymorphis bands. Two distinct clades generated from UPGMA dendrogram further investigate in Bayesian analysis using STRUCTURE software and estimated the population structure at optimal value K=4. Result show a present of four genetic structures in S. plicata population. Pahang and Terengganu population revealed a higher genetic variation (60.25%) indicating a possible hybridization between the Northern (Kedah), Southern (Negeri Sembilan and Johor) and Central (Selangor) region population. It is clear that geographical distance is the first factor to contribute distant population structures. The finding from the morphological and molecular data, show the conservation measures to cryopreserved S. plicata germplasm are important. However, due to limitation of time, optimization and lack of domestication measures implemented to grow the S. plicata ex situ resulted in low survival rate of the protocorm even though the encapsulation-vitrification technique has been established. Therefore, this study will need to be revisited in future once domestication process for this species has been implemented. This study resulted in characterisation of spathoglottis species using morphological and molecular marker for ease identification introducing the concept of varietal protection and conservation strategy and legislation for commercial of this valued species.